The story world - Tooze, Ruth; The Child's World (Chicago, Illinois : The Child's World, 1971)
Twenty-six poems and stories, many extracted from the longer works of Laura Ingalls Wilder, Eleanor Estes, Ruth Sawyer, Virginia Sorenson, Beverly Cleary and other writers.
Keywords: Children's literature; Children's stories; Literature -- Collections